(untitled) (Saúde Ética & Justiça, 2017)
This paper briefly analyses the Brazilian Code of Medical Ethics and also suggests a Code of Medical Ethics Principles, that would not be a code of rules but rather a code of principles. Although principles are more vaguer abstract than rules, they are more stable and less limited. Considering also that health is defined as a biopsychosocial well being and not only as the absence of illness, this paper purposes a code of principles for the health area, taking into account the principles of Bioethics: respect for the human being, the individual's freedom and autonomy, benefits related to quality of life and the usefulness of medical acts.